Case Report: Tropheryma whipplei Hide in an AIDS Patient With Pneumocystis Pneumonia - Yan, Jun; Zhang, Binhai; Zhang, Zhongdong; Shi, Jinchuan; Liu, Shourong; Qi, Jianjiang; Wang, Mengyan (Frontiers in Public Health, 2021)
Introduction: Pneumocystis pneumonia (PCP) is one of the most common opportunistic infections in HIV-infected patients. However, co-infection with Tropheryma whipplei is rare in AIDS patients with Pneumocystis pneumonia. Case presentation: We report a 28-year-old male AIDS patient co-infection with Tropheryma whipplei and Pneumocystis jirovecii diagnosed in bronchoalveolar lavage (BAL). After sulfamethoxazole-trimethoprim and meropenem treatment, the patient obtained obviously clinical improvement in two weeks. Conclusions: Clinicians need to be alert to the occurrence of Tropheryma whipplei infection in AIDS patients with Pneumocystis pneumonia and timely diagnosis and antibacterial treatments are essential.